1996
DOI: 10.1007/s004240050215
|View full text |Cite
|
Sign up to set email alerts
|

Whole-muscle and single-fibre contractile properties and myosin heavy chain isoforms in humans

Abstract: The contractile characteristics of three human muscle groups (triceps surae, quadriceps femoris and triceps brachii) of seven young male subjects were examined. The contractile properties were determined from electrically evoked isometric responses and compared with fibre type composition determined from needle biopsy samples. Fibre types were identified using myosin heavy chain (MHC) isoforms as molecular markers with gel electrophoresis (SDS-PAGE) and histochemical ATPase staining. Four contractile parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
279
4
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(329 citation statements)
references
References 37 publications
30
279
4
7
Order By: Relevance
“…However, the contractile properties were faster in males than females, particularly in rise and relaxation with tetanic stimulation. This is most likely caused by the increased proportion of MHC 2b fibers in the male ADM muscles, which is the fiber type that produces the fastest shortening velocity (16)(17)(18). This observation is consistent with previous characterizations of fiber type distributions in murine masticatory muscles (5,19), where male muscles are comprised of a greater proportion of MHC 2b fibers both in number and proportional area.…”
Section: Discussionsupporting
confidence: 91%
“…However, the contractile properties were faster in males than females, particularly in rise and relaxation with tetanic stimulation. This is most likely caused by the increased proportion of MHC 2b fibers in the male ADM muscles, which is the fiber type that produces the fastest shortening velocity (16)(17)(18). This observation is consistent with previous characterizations of fiber type distributions in murine masticatory muscles (5,19), where male muscles are comprised of a greater proportion of MHC 2b fibers both in number and proportional area.…”
Section: Discussionsupporting
confidence: 91%
“…Certainly, increases in muscle mass will improve peak power production by the muscle, irrespective of its fiber-type distribution. The proportion of fast-type fibers is also critical to peak power production because it determines maximal muscle-fiber contraction velocity (27,58,59). Optimal pedaling velocity during sprint cycling has been shown to relate to the proportion of fast-type fibers in musculus vastus lateralis (30) and their proportion of the cross-sectional area (31).…”
Section: Physiology Of Sprinters: High Normalized Sprint Performance mentioning
confidence: 99%
“…The muscle fibers that express MyHC-β are characterized as slow, fatigue resistant and oxidative (type 1 muscle fibers), whereas the fibers that express MyHC-2A are fast oxidative (type 2A muscle fibers), and the MyHC-2X fibers are fast glycolytic (type 2X muscle fibers). Most human muscles consist of all three muscle fiber types in varying degrees, depending on the functional demands of the muscle (Harridge, et al, 1996), age and gender (Schiaffino and Reggiani, 2011). Studies performed in rodents have demonstrated that MyHC isoforms expressed in differentiated myotubes were identical to the MyHC expression pattern in the muscle fibers from which the satellite cells were isolated (Dusterhoft andPette, 1993, Rosenblatt, et al, 1996).…”
Section: Fiber Type Comparisonmentioning
confidence: 99%